Urgensi Penerapan Metode Talqin Untuk Meningkatkan Kemampuan Menghafal Al-Quran di Pondok Tahfiz RBA Asy Syifa Curup - Panji Sultansyah Ibrahim; Ifnaldi Ifnaldi (IAIN Manado, 2022)
The Urgency of Applying the Talqin Method to Improve the Ability to Memorize Al-Quran at Pondok Tahfiz Rba Asy Syifa Curup. Becoming a hafiz or having a generation that memorizes the Al Quran is the hope of Muslims, because it is a virtue that can bring its owner happiness in this world and the hereafter. This research is motivated by the development of institutions or foundations and schools that hold Tahfidz Al Quran learning programs, one of which is Pondok Tahfiz RBA Asy Syifa Curup. The problem that often occurs with students is difficulty in memorizing the Koran and weakness in reciting the verses of the Koran well. This research is field research (Field Research) that is descriptive and qualitative in nature. Data collection techniques through observation, interviews, and documentation. Then the data analysis technique uses data reduction, data presentation, and conclusions or verification as well as testing the credibility of the data using source and technique (method) triangulation. The results of the research that we want to know are about the urgency of applying the talqin method in increasing students' memorization and looking at the quality of students' memorization at Pondok Tahfidz RBA Asy Syifa Curup.